Dream Interpretation Ancient and Modern : Notes from the Seminar Given in 1936-1941 - Updated Edition - Jung, C. G. (Carl Gustav), 1875-1961 (Book collections on Project MUSE., 2014)
From 1936 to 1941, C.G. Jung gave a four-part seminar series in Zurich on children's dreams and the historical literature on dream interpretation. This book completes the two-part publication of this landmark seminar, presenting the sessions devoted to dream interpretation and its history. Here we witness Jung as both clinician and teacher: impatient and sometimes authoritarian but also witty, wise, and intellectually daring, a man who, though brilliant, could be vulnerable, uncertain, and humbled by life's mysteries. These sessions open a window on Jungian dream interpretation in practice.